Monoclonal Gammopathy of Renal Significance with Progression to Multiple Myeloma in a Patient with ASIA-MO Syndrome - David Alejandro Vargas Gutiérrez; Karina Ivonne Arias Callejas; Edwin Pavel Palacios Ruiz; Priscila Joseline Pérez Vinueza; Juan Diego Muñoz Vega; Ana Karen G. Mejía Geraldo; Ingrid Salinas Zaldívar (Case Reports in Hematology)
Background. Autoimmune/inflammatory syndrome induced by adjuvants is a disease associated with an unregulated hyperactivity of the immune system and may also be associated with a high frequency of hematologic malignancies. Report. This is a case of a female with ASIA-MO syndrome secondary to infiltration of mineral oil for aesthetic purposes and presented with multiple episodes of urolithiasis resulting in renal impairment of her left kidney confirmed by scintigraphy and ending in unilateral nephrectomy. Retrospective renal piece analysis confirmed tubulointerstitial infiltration with light chains and plasma cells. Paraffin fixation prevented subsequent immunofluorescence analysis for better follow-up of the patient. Conclusion. The presence of positive immunofixation kappa chains explained the sudden deterioration of renal function with monoclonal gammopathy of renal significance which concluded in an association between diseases, such as multiple light chain myeloma, as a final diagnosis.